Analisis Tingkat Kerawanan Kebakaran Permukiman Dengan Pemanfaatan Sistem Informasi Geografis Di Kecamatan Pakualaman, Kota Yogyakarta - Yunita, Erma, Drs. Munawar Cholil, M.Si, Agus Anggoro Sigit, S.Si., M.Sc (2015)
This study aims to : 1 ) Determine the level of vulnerability to fire agihan in District Pakualaman . 2 ) Analyze the factors that play a dominant role in influencing agihan large fires in the district -level vulnerability Pakualaman . The method used in this study is a survey method in doing the survey method to obtain the data and if the data is not obtained from the agency on the go then do the field survey , the survey method using stratified random sampling method . Stratified random sampling method is a method by which to determine sample done at random on the basis of strata that have been made ( at random with a corresponding proportion of the amount in each stratum ) . Analysis of data using quantitative analysis method with a tiered approach , this method is a method that uses the dignity administration and calculation of scores on each of its parameters to determine the level of vulnerability agihan fire and the dominant factor influencing the level of vulnerability to fire . In the process of data processing utilizing geographic information system include buffering , scoring , overlay and dissolve . Based on the analysis of research Map Fire Vulnerability Level Settlement With Utilization of Geographic Information Systems in Sub Pakualaman , Yogyakarta . Are classified into three classes, namely the vulnerability of low, moderate impact and high vulnerability. Purwokinanti Village is a village with the vulnerability of the fire as much as 68 % and as much as 32 % Gunungketur village.